Simulação numérica do fluxo hídrico subterrâneo na bacia hidrográfica do Rio Pitimbu RN - Mousinho, David da Silveira (2012)
Urban centers in Pitimbu Watershed use significant groundwater sources for public supply. Therefore, studies in Dunas Barreiras aquifer are relevant to expand knowledge about it and help manage water resources in the region. An essential tool for this management is the numerical modeling of groundwater flow. In this work, we developed a groundwater flow model for Pitimbu Watershed, using the Visual Modflow, version 2.7.1., which uses finite difference method for solving the govern equation of the dynamics of groundwater flow. We carried out the numerical simulation of steady-state model for the entire region of the basin. The model was built in the geographical, geomorphological and hydrogeological study of the area, which defined the boundary conditions and the parameters required for the numerical calculation. Owing to unavailability of current data based on monitoring of the aquifer it was not possible to calibrate the model. However, the simulation results showed that the overall water balance approached zero, therefore satisfying the equation for the three-dimensional behavior of the head water in steady state. Variations in aquifer recharge data were made to verify the impact of this contribution on the water balance of the system, especially in the scenario in which recharge due to drains and sinks was removed. According to the results generated by Visual Modflow occurred significantly hydraulic head lowering, ranging from 16,4 to 82 feet of drawdown. With the results obtained, it can be said that modeling is performed as a valid tool for the management of water resources in Pitimbu River Basin, and to support new studies